2004
DOI: 10.1080/15216540410001727699
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine and MDMA (Ecstasy) Neurotoxicity: 'of Mice and Men'

Abstract: SummaryMethamphetamine (METH) and 3,4-meythylenedioxymethamphetamine (MDMA; 'ecstasy') are currently major drugs of abuse. One of the major concerns of amphetamines abuse is their potential neurotoxic effect on dopaminergic and serotonergic neurons. Although data from human studies are somewhat limited, compelling evidence suggests that these drugs cause neurotoxicity in rodents and primates. Recent studies in transgenic and knockout mice identified the role of dopamine transporters, nitric oxide, apoptotic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 42 publications
2
41
0
Order By: Relevance
“…Administration of METH (5 mg/kg  3) to Swiss Webster mice resulted in 42-61% depletion of DA and DAT in the striatum, frontal cortex and amygdala (Achat-Mendes et al, 2005;Itzhak and Achat-Mendes, 2004). In the present study, dopaminergic neurotoxicity was confirmed by the marked reduction of striatal TH-immunoreactive neurons and the significant increase in GFAP expression 5 days after METH administration to Swiss Webster mice (Figure 1).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Administration of METH (5 mg/kg  3) to Swiss Webster mice resulted in 42-61% depletion of DA and DAT in the striatum, frontal cortex and amygdala (Achat-Mendes et al, 2005;Itzhak and Achat-Mendes, 2004). In the present study, dopaminergic neurotoxicity was confirmed by the marked reduction of striatal TH-immunoreactive neurons and the significant increase in GFAP expression 5 days after METH administration to Swiss Webster mice (Figure 1).…”
Section: Discussionsupporting
confidence: 65%
“…We have previously shown that METH (5 mg/kg  3; 3 h apart) resulted in 42-61% depletion of DA-and DAT-binding sites in striatum, frontal cortex and amygdala of Swiss Webster mice (Achat-Mendes et al, 2005). Selective dopaminergic neurotoxicity with no evidence of serotonergic neurotoxicity (Itzhak and Achat-Mendes, 2004) was sustained for 95 days following METH administration to Swiss Webster mice (Itzhak et al, 2002). In the present study, METH-induced dopaminergic neurotoxicity was confirmed by immunohistochemical studies.…”
Section: Pretraining Dopaminergic Neurotoxicitymentioning
confidence: 99%
“…Results from studies in humans, non-human primates and rodents support the view that these compounds cause structural damage to monoamine nerve terminals and are thereby neurotoxic (O'Callaghan, 2002a, Lyles and Cadet, 2003, Itzhak and Achat-Mendes, 2004. Such data include the finding that repeated high-dose administration of METH results in a reduction in striatal dopamine (DA) and serotonin (5-HT) concentrations (Kogan et al, 1976, Wagner et al, 1980, a decrease in the activity of tyrosine and tryptophan hydroxylase, the rate-limiting enzymes responsible for the production of DA and 5-HT (Hotchkiss and Gibb, 1980), and reduced number of amine uptake sites (Wagner et al, 1980).…”
supporting
confidence: 56%
“…Importantly, in the mouse, MDMA is much more of a dopaminergic agent than it appears to be in other species, eliciting neurochemical and behavioral effects similar to those of METH after both acute and chronic treatment (O'Callaghan and Miller, 1994;Mann et al, 1997;Itzhak and Achat-Mendes, 2004;Fantegrossi et al, 2008;Panas et al, 2010;Granado et al, 2011;Murnane et al, 2012). These observed similarities between the effects of MDMA and METH are likely because of similar neuropharmacology of these compounds in the mouse.…”
Section: Introductionmentioning
confidence: 63%